IDENTIFICATION OF PREDICTORS OF MIGRAINOUS STROKE AND DEVELOPMENT OF PREVENTIVE MEASURES FOR HIGH-RISK INDIVIDUALS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review summarizes key predictors of migrainous stroke, including female gender, young age, migraine with aura, hormonal contraceptive use, smoking, hypertension, and genetic factors. It outlines the underlying mechanisms such as cortical spreading depression and vascular inflammation. Preventive strategies focus on lifestyle changes, contraceptive counseling, antiplatelet therapy, and migraine prophylaxis. Risk models help identify high-risk individuals for personalized prevention. A multidisciplinary approach involving neurology, gynecology, and primary care is recommended. Future research aims to develop risk prediction tools, discover new biomarkers, and advance precision medicine.